How size matters: exploring the association between quality of mental health services and catchment area size - Ala-Nikkola T; Sadeniemi M; Kaila M; Saarni S; Kontio R; Pirkola S; Joffe G; Oranta O; Wahlbeck K (BIOMED CENTRAL LTD, 2022)
Background: The diversity of mental health and substance abuse services (MHS) available to service users is seen as an indicator of the quality of the service system. In most countries MHS are provided by a mix of public, private and third sector providers. In Finland, officially, the municipalities are responsible for organizing the services needed, but the real extent and roles of private and third sector service providers are not known. Our previous study showed that the catchment area population size was strongly associated with diversity of mental health services. It is not known whether this was due to some types of services or some provider types being more sensitive to the size effect than others.The aim of this study was to investigate the association between area population size and diversity of mental health services, i.e. which types of services and which service providers' contributions are sensitive to population size.Methods: To map and classify services, we used the ESMS-R. The diversity of services was defined as the count of main types of care. Providers were classified as public, private or third sectors.Results: The diversity of outpatient, residential and voluntary services correlated positively with catchment area population size. The strongest positive correlation between the size of population and services available was found in third sector activities followed by public providers, but no correlation was found for diversity of private services. The third sector and public corporations each provided 44 % of the service units.Third sector providers produced all self-help services and most of the day care services. Third sector and private companies provided a significant part (59 %) of the residential care service units.Conclusions: Significant positive correlations were found between size of catchment area population and diversity of residential, outpatient and voluntary services, indicating that these services concentrate on areas with larger population bases. The third sector seems to significantly complement the public sector in providing different services. Thus the third sector be needs to be functionally integrated with other MHS services to achieve a diversified and integrated service system.